2020
DOI: 10.3390/ma13051234
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical Mini-Review on the Compression Strength of Rubberized Concrete as a Function of the Amount of Recycled Tires Crumb Rubber

Abstract: Since waste tires constitute a serious environmental concern, several studies are devoted to the use of finely divided recycled rubber for the production of rubberized concrete by partial substitution of the mineral aggregate fraction. The introduction of rubber into concrete presents several advantages (e.g., improvement of toughness and thermal/electrical/acoustic insulation capacities). Unfortunately, the addition of a high content of rubber into concrete causes an important loss of mechanical resistance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 71 publications
(116 reference statements)
0
19
1
Order By: Relevance
“…There is some correlation between the results of the study and existing literature, with variations in the upper/lower bounds of compressive strength reduction. However, the results stand in contrast to the findings of some other researchers [13] who found that compressive strength, among other properties, was improved by the introduction of SR into the mix. Figure 8b shows the variation of compressive strength of samples containing CR compared with the benchmark at the 7-and 28-day marks.…”
Section: Modulus Of Rupturecontrasting
confidence: 99%
See 2 more Smart Citations
“…There is some correlation between the results of the study and existing literature, with variations in the upper/lower bounds of compressive strength reduction. However, the results stand in contrast to the findings of some other researchers [13] who found that compressive strength, among other properties, was improved by the introduction of SR into the mix. Figure 8b shows the variation of compressive strength of samples containing CR compared with the benchmark at the 7-and 28-day marks.…”
Section: Modulus Of Rupturecontrasting
confidence: 99%
“…Due to an exponential growth in the use of cars in Kuwait, the accumulation of used tires poses a serious risk to the ecosystem; therefore, recycling waste products is vital [8][9][10]. Recently, great effort has been directed toward finding alternate ways to use waste materials emerging in the world [11][12][13]. Researchers have found that the recycling of waste rubber tires has several environmental and economic advantages [11,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in the quantity of synthetic fibers above such level results in the worsening of the mechanical properties of modified concrete. There is also much information on the use of waste polystyrene [ 29 , 30 , 31 , 32 ] and rubber [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] to manufacture concrete. Along with the increase in the quantity of rubber waste used as a substitute for sand, concrete mixtures are characterized with lower [ 36 , 37 , 38 , 39 , 40 , 41 ] or higher [ 34 ] workability.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, tires landfilling was forbidden with the European Council Directive 1999/ 31/CE due to its dangerous impact on the environment and human health [2,3]. Furthermore, sustainable and circular economy principles have growth leading to the exploration of alternatives end-life tires processes [4].…”
Section: Introductionmentioning
confidence: 99%